INNOVATIVE APPROACH TO CONDUCT TRAINING EXERCISES IN EDUCATION - Teshaeva Kamola Rajabobna (Web of Journals Publishing, 2024)
The article discusses the relevance, theoretical and practical importance of effective formation of cognitive and behavioral characteristics of the student through the rational use of social-educational, psychological training, exercises and didactic games in classes in accordance with different age periods.
Keywords: Training, social-educational, psychological training.